Influenza Vaccine Effectiveness Against Hospitalization in the United States, 2019–2020. (30th December 2020) - Tenforde, Mark W; Talbot, H Keipp; Trabue, Christopher H; Gaglani, Manjusha; McNeal, Tresa M; Monto, Arnold S; Martin, Emily T; Zimmerman, Richard K; Silveira, Fernanda P; Middleton, Donald B; Olson, Samantha M; Garten Kondor, Rebecca J; et al.
Abstract: Background: Influenza causes significant morbidity and mortality and stresses hospital resources during periods of increased circulation. We evaluated the effectiveness of the 2019–2020 influenza vaccine against influenza-associated hospitalization in the United States. Methods: We included adults hospitalized with acute respiratory illness at 14 hospitals and tested for influenza viruses by reserve-transcription polymerase chain reaction. Vaccine effectiveness (VE) was estimated by comparing the odds of current-season influenza vaccination in test-positive influenza cases vs test-negative controls, adjusting for confounders. VE was stratified by age and major circulating influenza types along with A(H1N1)pdm09 genetic subgroups. Results: A total of 3116 participants were included, including 18% (n = 553) influenza-positive cases. Median age was 63 years. Sixty-seven percent (n = 2079) received vaccination. Overall adjusted VE against influenza viruses was 41% (95% confidence interval [CI], 27%–52%). VE against A(H1N1)pdm09 viruses was 40% (95% CI, 24%–53%) and 33% against B viruses (95% CI, 0–56%). Of the 2 major A(H1N1)pdm09 subgroups (representing 90% of sequenced H1N1 viruses), VE against one group (5A + 187A, 189E) was 59% (95% CI, 34%–75%) whereas no VE was observed against the other group (5A + 156K) (–1% [95% CI, –61% to 37%]). Conclusions: In a primarily older population, influenza vaccination was associated with a 41% reduction in risk of hospitalized influenza illness. Abstract : During the 2019-2020 United States influenza season, genetically diverse influenza A(H1N1)pdm09 and influenza B viruses of the Victoria lineage co-circulated. Overall vaccine effectiveness against influenza-associated hospitalization was 41% despite circulation of multiple antigenically drifted viruses.